2021
DOI: 10.1051/sicotj/2021052
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosed cartilaginous PCL avulsion in young children

Abstract: Posterior Cruciate Ligaments injuries are rare in children and usually due to bony avulsion fractures or midsubstance tears. This study focused on cartilaginous avulsions initially misdiagnosed despite of MRI assessment. Two 6-year-old boys had cartilaginous avulsion fracture injury at the femoral attachment of the PCL. One had associated medial meniscal lesion and was reinserted. The other conducted to non-union. MRI second lecture reveals an original description with nail-biting sign on cartilage surface of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In 2021, Pacull et al identified 14 patients younger than 9 years with PCL cartilaginous injuries (cartilaginous avulsion or intrasubstance tear) 8 . In pediatric and adolescent patients, tibial PCL avulsions are more common than femoral PCL avulsions 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, Pacull et al identified 14 patients younger than 9 years with PCL cartilaginous injuries (cartilaginous avulsion or intrasubstance tear) 8 . In pediatric and adolescent patients, tibial PCL avulsions are more common than femoral PCL avulsions 6 .…”
Section: Discussionmentioning
confidence: 99%
“…In patients younger than 14 years, most PCL femoral avulsions described are cartilaginous, and several have been reported in children aged 3 to 7 years 7,8 . Five bony femoral avulsion fractures are reported in the literature; however, they were in patients 8 years or older, and their mechanisms of injury were typically secondary to high-energy trauma 9-13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly in frontal aggression in the flexed knee posture or hyperextension, the PCL is vulnerable to injury. The PCL is involved in 4%-38% of knee injuries observed in emergency rooms, indicating the clinical importance of this ligament in preserving knee joint integrity [7]. Avulsion fractures of the tibial insertion caused by the posterior cruciate ligament (PCL) are extremely uncommon in pediatric patients.…”
Section: Introductionmentioning
confidence: 99%